Effect of Temperature On The Dissociation Of Cysteine In Aqueous Solutions From Conductivity Measurements - AI-Taiar, A.H.; Bhaya, N.D.; Ridha, S.H.; AIÂ Sammarrie, H.B.; AI-Fakhry, K.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The conductance of solu ti ons of cysteine in water at different concentrations and temperatures has been measured. These solutions obey Onsagcr equation and give linear relations especially at low concentrations. In more concentrated solutions a deviation from the equation is observed. The molar conductivity of these solutions decreases with t he increase in concen trations at constant temperature. The values of the ionization constants and the conductivity at infin ite dilution for each temperature have been calcu lated.